Copper(I)‐Catalyzed Cascade Cyclization to the Total Synthesis of Hexahydropyrroloindole Alkaloids: Flustramine B and Debromoflustramine B. Issue 21 (1st June 2021) - Shen, Xianfu; Peng, Tianfeng; Wang, Fan; Li, Shumin; Lei, Xingfu; Yunxiao,; Wang,; Cheng, Feixiang; Liu, Teng
Abstract: In this report, we have accomplished the total synthesis of two bioactive hexahydropyrroloindole (HPI) alkaloids bearing a C3a tetrasubstituted stereocenters substituted by isopentenyl. This route was based on Cu‐catalyzed cascade arylation‐alkylation sequence in one‐pot as a key step, providing Flustramine B and Debromoflustramine B with 9 steps in 37.6 % and 31.1 % overall yields, respectively. Abstract : Copper(I)‐Catalyzed Cascade Cyclization to the Total Synthesis of Hexahydropyrroloindole Alkaloids: Flustramine B and Debromoflustramine B In this work, we have accomplished the total synthesis of two bioactive hexahydropyrroloindole (HPI) alkaloids bearing a C3a tetrasubstituted stereocenters substituted by isopentenyl. Our route was based on Cu‐catalyzed cascade arylation‐alkylation sequence in one‐pot as a key step, providing Flustramine B and Debromoflustramine B with 9 steps in 37.6 % and 31.1 % overall yields, respectively.